Home-Based Exercise to Habitual Physical Activity Strategies for Elderly with Sarcopenia: A Literature Review - Ni Kadek Yuni Fridayani; Yuliana Restu Tulak; Cheuk Hin Ho (Universitas Udayana dan Diaspora Taipei Medical University, 2021)
Background: Sarcopenia’s definition are low muscle strength, low muscle quantity or quality, and low muscle performance. Several studies have found that skeletal mass can decrease as a result of a lack of physical activity and it along have to increase risk of adverse outcomes including falls, frailty, disability, morbidity and mortality. Exercise interventions is the most effective strategy for increasing the skeletal muscle mass and maintain functional independence of elderly people. In this review will discuss about how physical activity be a habitual exercise that less cost and easy to do, will be home based exercise for elderly people with sarcopenia to decrease of exacerbate. Methods: The literature had selected studies from the following databases: PubMed, Google Scholar and PEDro. We explored evidence which relevant topic using the following database with keyword ‘sarcopenia and pre-sarcopenia’, ‘exercise for sarcopenia and pre-sarcopenia’, 'home-based exercise’, ‘physical activity for elderly’, ‘elderly with sarcopenia’ and selection by inclusion and exclusion criteria. Results: Four studies were corresponded with home exercise-based habitual physical activity for people with pre sarcopenia and prevent sarcopenia which have been analyzed as results of the study. The habitual physical activity that can be home based exercise for prevent decreasing of muscle mass in elderly people are exercise snacking, stretching exercise, walking and tele exercise. All of the exercises showed significantly increased muscle mass and were easy to do, and those safety. The easiest is exercise snacking, but stretching exercise and walking around are more effective to increase the muscle mass and muscle strength compared to exercise snacking along. Conclusion: Sarcopenia can be prevented in older adults with in home-based exercise from habitual physical activity such as exercise snacking, stretching exercise, walking around, and tele-exercise.